2001
DOI: 10.1055/s-2001-16802
|View full text |Cite
|
Sign up to set email alerts
|

Biphenylphosphine-Palladium(II) Complexes-Catalyzed Friedel-Crafts Reaction for the Synthesis of α-Amino and α-Hydroxy Indolylacetates and Diindolylacetates

Abstract: Biphenylphosphine-palladium(II) complexes-catalyzed Friedel-Crafts reaction of N-methylindol with imino and carbonyl compounds afforded a-amino and a-hydroxy substituted indolylacetates and diindolylacetates in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 4 publications
0
21
0
1
Order By: Relevance
“…Nevertheless, Mikami and co-workers reported in 2001 that biphenylphosphine-palladium(II) could successfully catalyze Friedel-Crafts reaction of indoles with glyoxylate to generate indolylacetates or bisindolylacetates as the main product, depending on the reaction conditions. [17] In 2002, Jørgensens group demonstrated that heteroaromatic compounds, including indoles, reacted with ethyl glyoxylate to give Friedel-Crafts addition adducts in good yields in various aqueous media. [18] During the preparation of this manuscript, Deng and co-workers reported enantioselective Friedel-Crafts reactions of indoles with carbonyl compounds catalyzed by bifunctional Cinchona alkaloids.…”
Section: Asymmetric Friedel-crafts Alkylations Of Indoles With Ethyl mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Mikami and co-workers reported in 2001 that biphenylphosphine-palladium(II) could successfully catalyze Friedel-Crafts reaction of indoles with glyoxylate to generate indolylacetates or bisindolylacetates as the main product, depending on the reaction conditions. [17] In 2002, Jørgensens group demonstrated that heteroaromatic compounds, including indoles, reacted with ethyl glyoxylate to give Friedel-Crafts addition adducts in good yields in various aqueous media. [18] During the preparation of this manuscript, Deng and co-workers reported enantioselective Friedel-Crafts reactions of indoles with carbonyl compounds catalyzed by bifunctional Cinchona alkaloids.…”
Section: Asymmetric Friedel-crafts Alkylations Of Indoles With Ethyl mentioning
confidence: 99%
“…In the following steps, intermediate 11 may follow pathway I [17] to give the undesired bisindole product (3a') or follow pathway II to provide the expected product (3a) and release the chiral catalyst for the catalytic cycles. Under our conditions, the pathway I may be suppressed at lower temperature.…”
Section: Asymmetric Friedel-crafts Alkylations Of Indoles With Ethyl mentioning
confidence: 99%
“…α‐(3‐Indolyl)glycines ( 86 ; R 1 : H, R 2 : CO 2 R) are an important family of synthetic intermediates for the preparation of nonproteinogenic amino acids 97c,d,f. Indolylglycines can be conveniently obtained as a racemic mixture by spontaneous98, 99a,b or catalyzed99c Friedel–Crafts alkylation of indoles with preformed or in situ prepared glyoxylate imines. Good levels of diastereoselectivity can be achieved when preformed alkylating agents are used by introducing a chiral auxiliary on the imine 98a.…”
Section: Reaction With Cx Bondsmentioning
confidence: 99%
“…The Friedel-Crafts-type reactions of N-methylindole with ethyl glyoxylate 51 are catalyzed by the Lewis acidity of Pd(II) complexes [183]. Unprecedentedly,…”
Section: Catalytic Asymmetric Friedel-crafts Reactionmentioning
confidence: 99%